Wysteria: A Programming Language for Generic, Mixed-Mode Multiparty Computations - Rastogi, Aseem; Hammer, Matthew A.; Hicks, Michael (SP '14 Proceedings of the 2014 IEEE Symposium on Security and Privacy, 2014)
In a Secure Multiparty Computation (SMC), mutually distrusting parties use cryptographic techniques to cooperatively compute over their private data, in the process each party learns only explicitly revealed outputs. In this paper, we present Wysteria, a high-level programming language for writing SMCs. As with past languages, like Fairplay, Wysteria compiles secure computations to circuits that are executed by an underlying engine. Unlike past work, Wysteria provides support for mixed-mode programs, which combine local, private computations with synchronous SMCs. Wysteria complements a standard feature set with built-in support for secret shares and with wire bundles, a new abstraction that supports generic n-party computations. We have formalized Wysteria, its refinement type system, and its operational semantics. We show that Wysteria programs have an easy-to-understand single-threaded interpretation and prove that this view corresponds to the actual multi-threaded semantics. We also prove type soundness, a property we show has security ramifications, namely that information about one party's data can only be revealed to another via (agreed upon) secure computations. We have implemented Wysteria, and used it to program a variety of interesting SMC protocols from the literature, as well as several new ones. We find that Wysteria's performance is competitive with prior approaches while making programming far easier, and more trustworthy.